2020
DOI: 10.1089/lrb.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Body Positional Effects on Bioimpedance Spectroscopy Measurements for Lymphedema Assessment of the Arm

Abstract: Background: Bioimpedance spectroscopy (BIS) measurements have conventionally been performed using a device that uses gel-backed electrodes with the patient in a supine position. More recently, impedance devices that use stainless steel electrodes with the patient in a standing position have become available. The aim of this study was to assess and compare BIS measurements made in three different body positions using two different impedance devices (lead device and stand-on device) in women with and without arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…12,13 BIS, particularly when performed using newer upright scale-like devices, provides immediate reproducible and objective feedback and can be done by any trained staff members in a few minutes. 14 Studies have found that BIS is a reliable objective measure for patients with early lymphedema with a score of >7.1, consistent with clinical BCRL. 12 BIS, particularly when performed using newer upright scale-like devices, provides immediate feedback and can be done by any trained staff in a few minutes.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…12,13 BIS, particularly when performed using newer upright scale-like devices, provides immediate reproducible and objective feedback and can be done by any trained staff members in a few minutes. 14 Studies have found that BIS is a reliable objective measure for patients with early lymphedema with a score of >7.1, consistent with clinical BCRL. 12 BIS, particularly when performed using newer upright scale-like devices, provides immediate feedback and can be done by any trained staff in a few minutes.…”
Section: Introductionmentioning
confidence: 67%
“…12 BIS, particularly when performed using newer upright scale-like devices, provides immediate feedback and can be done by any trained staff in a few minutes. 14 Ridner (2019) compared early detection using TM or BIS over 3 years in a multicenter international randomized control trial. Trigger points defining sBCRL requiring intervention were a BIS change of !6.5 L-Dex units and, for the TM group, a volume change in the at-risk arm that was between !5 and <10% above presurgical baselines (without a similar change in the noneat-risk arm).…”
Section: Introductionmentioning
confidence: 99%
“…BIS monitoring involved the use of a BIS stand-on device. The stand-on device used was a commercially available impedance device (SOZO ® , ImpediMed Limited, Brisbane, Australia) with demonstrated validity and reliability [28]. BIS measures the resistance at 0 kHz (R0) of the unaffected limb and compares this to the resistance at 0 kHz of the affected/at-risk limb expressed as the following ratio (unaffected:affected/at-risk).…”
Section: Interventionmentioning
confidence: 99%
“…They were excluded if they had implantable devices such as pacemaker or other inbuilt stimulator, were pregnant, reported having a previous history of breast cancer or arm lymphoedema, if they had a health condition that may affect body fluid status or if they reported having a psychiatric illness that would limit their compliance with study requirements The intervention consisted of a package including BIS monitoring, education, and support to promote self-management and physical activity over a 6-month period Item 3: What (Materials): any physical or informational materials used in the intervention, including those provided to participants or used in intervention delivery or in training of intervention providers BIS monitoring involved the use of a BIS stand-on device. The stand-on device used was a commercially available impedance device (SOZO®, ImpediMed Limited, Brisbane, Australia) with demonstrated validity and reliability [ 28 ]. This device is portable and can be operated easily by an individual completing self-measurements within a home environment with access to power and a wireless internet network Electronic scales were used so that the participant could take their weight prior to a BIS measurement The education component focussed on risk minimisation and included provision of the Australian Cancer Council Understanding Lymphoedema fact sheet [ 27 ] Self-management strategies included skin care, exercise, self-lymphatic drainage massage, compression and the use of pneumatic compression.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation